Surface laser-glazing of plasma-sprayed thermal barrier coatings - Batista, C. (2005)
Atmospheric plasma-sprayed (APS) ZrO2–8%WtY2O3 thermal barrier coatings (TBCs) were subjected to a CO2 continuous wave laser-glazing process in order to generate an external dense layer produced by different processing parameters. For that purpose, different beam scanning speeds and track overlapping were chosen. Surface roughness has been reduced significantly after laser-glazing. Despite the surface crack network, all laser-glazed specimens presented a fully dense and porous free external layer with a columnar microstructure. Surface cracks along the densified layer were found to have tendency to be oriented in two perpendicular directions, one in the direction of the laser beam travel, the other perpendicular to it. Moreover, the cracks parallel to the beam moving direction are found to be on the overlapping zone, coinciding with the edge of the subsequent track. The cracks along the densified layer are vertical and tend to branch and deviate from the vertical direction within the porous PS coating. The largest overlapping allied to the smallest amount of irradiated energy generated the most uniform layer with the shortest crack branches within the PS coating. For the as-sprayed coating, the XRD results revealed mainly t0 non-transformable tetragonal zirconia with a small percentage of residual monoclinic zirconia. All glazed coatings presented only t0 non-transformable tetragonal zirconia with some variations on preferable crystal orientation.